Towards the rational design of antimicrobial proteins: Single point mutations can switch on bactericidal and agglutinating activities on the RNase A superfamily lineage. (8th October 2013) - Pulido, David; Moussaoui, Mohammed; Nogués, M. Victòria; Torrent, Marc; Boix, Ester
Abstract : The ribonuclease (RNase) A superfamily lineage includes distant members with antimicrobial properties, suggesting a common ancestral host‐defense role. In an effort to identify the minimal requirements for the eosinophil cationic protein (ECP or RNase 3) antimicrobial properties we applied site‐directed mutagenesis on its closest family homolog, the eosinophil‐derived neurotoxin (EDN or RNase 2). Both eosinophil secretion proteins are involved in human immune defense, and are reported as being among the most rapidly evolving coding sequences in primates. Previous studies in our laboratory defined two regions at the N–terminus involved in the protein antimicrobial action, encompassing residues 8–16 and 34–36. Here, we demonstrate that switching two single residues is enough to provide EDN with ECP antipathogen properties. That is, the EDN double‐mutant Q34R/R35W displays enhanced bactericidal activity, particularly towards Gram‐negative bacteria, and a significant increase in its affinity towards the bacterial outer membrane lipopolysaccharides. Moreover, we confirmed the direct contribution of residue W35 in lipopolysaccharide binding, membrane interaction and permeabilization processes. Furthermore, additional T13 to I substitution provides EDN with an exposed hydrophobic patch required for protein self‐aggregation and triggers bacterial agglutination, thereby increasing the final antimicrobial activity by up to 20–fold. Our results highlight how single selected mutations can reshape the entire protein function. This study provides an example of how structure‐guided protein engineering can successfully reproduce an evolution selection process towards the emergence of new physiological roles. Abstract : We have designed an EDN double mutant, Q34R/R35W, which displays enhanced bactericidal activity and a significant increase on lipopolysaccharide affinity. One additional mutation, T13I, provides EDN with an exposed hydrophobic patch required for self‐aggregation that triggers bacteria agglutination. Our results highlight how structure guided protein engineering can successfully reproduce an evolution selection process towards the emergence of new physiological roles.